Density functional theory study of graphene - Huang, Lin (2016)
In this thesis we mainly focus on : (a) band gap manipulation of monolayer graphene by phenyl radical adsorption; (b) controlling armchair and zigzag edges in oxidative cutting of graphene with strain; (c) understanding of their photoluminescence (PL) mechanisms of graphene quantum dots (GQDs) using density functional theory (DFT) and time-dependent DFT (TDDFT) calculations. We observe that (a) the adsorption of single phenyl radical breaks the aromatic π-bond of graphene and generates an unpaired electron which is delocalized on ortho or para positions, (b) the adsorption of the second phenyl radical at ortho or para position saturates the generated unpair electron by electron pairing and results in semiconducting graphene, (c) adsorption of more even numbers of phenyl radicals on graphene by ortho-ortho and ortho-para pairings increases the band gap of graphene. We have also investigated the oxidation of graphene considering the adsorption at both sides of graphene sheet. We show that (1) the formation of armchair epoxy chain on graphene sheet is energetically favorable when the oxidation is occurred on both sides of graphene sheet, (2) whereas formation of zigzag epoxy chain is favorable when oxidation occurred on the same side of graphene, (3) when external strain is applied on graphene the zigzag epoxy chain formation on graphene sheet becomes energetically more favorable. We have also studied the PL properties of GQDs using both DFT TDDFT calculations to reveal the PL mechanism and also investigated the effect of size, edge configurations, shapes, attached chemical functionalities, heteroatom dopings and defects on PL properties of GQDs.